Enhancing fire disaster management: Innovative approaches using physical peatland monitoring data - Prayoga, M. Bayu Rizky; Karuniasa, Mahawan; Frimawaty, Evi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: In Indonesia, the persistent occurrence of forest and land fires highlights the critical importance of early detection in determining the success of mitigation efforts. Method: This study explores several key aspects related to peatland wetness and its impact on fire prevention. Firstly, it examines the relationship between rainfall and the humidity and temperature of peatlands. Secondly, the study investigates peatland wetness as an indicator of hotspot emergence. Thirdly, the study evaluates stakeholder perceptions regarding the use of peat wetness monitoring in determining the emergency status of forest and land fire disasters. Findings: The study's results indicate that rainfall significantly influences peatland humidity, which in turn reflects the level of peat humidity and temperature. It was also found that peatlands with a Dry-Moderate humidity category can be a reliable indicator of the emergence of fire spots. The consensus among stakeholders is that monitoring peatland humidity is very important for decision-making related to emergency status. Finally, this study proposes a forest and land fire mitigation concept based on peatland humidity. Conclusion: This approach aims to reduce the risk of such fires by utilizing monitoring results to enhance preparedness, taking into consideration the current state of peatland wetness. Overall, this research underscores the importance of integrating peatland wetness monitoring into forest and land fire mitigation strategies to improve early detection and reduce the risk of fires. Novelty/Originality of this study: A study of forest fires in Indonesia links peatland wetness to fire hotspots, providing a reliable indicator for early fire detection. This is an innovative approach to forest fire prevention.